Effects of pylometric training on jumping performance in junior basketball players - Matavulj, D.; Kukolj, M.; Ugarkovic, D.; Tihanyi, J.; Jaric, S. (The Journal of Sports Medicine and Physical Fitness, 2001)
Although the plyometric training has proved its efficiency, it remains generally unknown whether a limited amount of plyometric training could improve movements in subjects who already demonstrate high level of performance. METHODS: Three different training regimens were performed in order to study effects of plyometric training on elite junior basketball players. While control group (CG) participated only in the regular midseason training activity, another two groups performed a limited amount of plyometric training employing drop jumps from the height of either 50 cm (EG-50) or 100 cm (EG-100). The height of the maximal vertical jump (CMJ), as well as the maximal voluntary force (F) and the rate of force development (RFD) of hip and knee extensors were tested prior to and after the training. RESULTS: An increase in CMJ (4.8 and 5.6 cm in EG-50 and EG-100, respectively), as well as in F of hip extensors and RFD of knee extensors was observed in both experimental groups, while no significant changes were recorded in CG. When the pretest scores were used as a covariate, both experimental groups demonstrated higher increase in CMJ and RFD of knee extensors then CG. However, no differences were observed between EG-50 and EG-100. The multiple correlation between four isometric parameters and CMJ revealed R2=0.29. CONCLUSIONS: A limited amount of plyometric training could improve jumping performance in elite junior basketball players and this improvement could be partly related with an increase in F of hip extensors and RFD of knee extensors. However, neither of the two initial heights of the applied drop jumps proved to be more effective.